2013
DOI: 10.1002/anie.201300137
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium‐Catalyzed Asymmetric Arylative Cyclization of meso‐1,6‐Dienynes Leading to Enantioenriched cis‐Hydrobenzofurans

Abstract: Chiral cis-hydrobenzofurans represent a unique motif existing in numerous natural products, for instance, isoambrox, [1] haterumaimide I, [2] rosenonolactone, [3] incarviditone, [4] and millingtonine A [5] (Scheme 1 a). Owing to their diverse biological activities, [1][2][3][4][5] a great deal of attention has been paid to the development of efficient methods toward their enantioselective syntheses. One of the most straightforward and powerful ways to construct such a framework is the catalytic asymmetric desy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(30 citation statements)
references
References 69 publications
0
29
0
1
Order By: Relevance
“…Meantime, the main side product, p ‐cresol was also observed, which was presumably attributed to the direct conjugate borylation to enone and succedent β‐O elimination. Next, several chiral phosphine ligands, including ( S , S p)‐ip‐FOXAP ( L2 ), ( R )‐BINAP ( L3 ), ( R )‐P‐Phos ( L4 ) and ( R , R )‐iPr‐DuPhos ( L5 ) were subjected to this reaction, however, no promising outcomes were gave (Table , entries 2–5). To our delight, the ee value of 3 a dramatically rose up to 74%, albeit in low yield, when ( R , R )‐QuinoxP* ( L6 ) served as ligand (Table , entry 6).…”
Section: Methodsmentioning
confidence: 99%
“…Meantime, the main side product, p ‐cresol was also observed, which was presumably attributed to the direct conjugate borylation to enone and succedent β‐O elimination. Next, several chiral phosphine ligands, including ( S , S p)‐ip‐FOXAP ( L2 ), ( R )‐BINAP ( L3 ), ( R )‐P‐Phos ( L4 ) and ( R , R )‐iPr‐DuPhos ( L5 ) were subjected to this reaction, however, no promising outcomes were gave (Table , entries 2–5). To our delight, the ee value of 3 a dramatically rose up to 74%, albeit in low yield, when ( R , R )‐QuinoxP* ( L6 ) served as ligand (Table , entry 6).…”
Section: Methodsmentioning
confidence: 99%
“…27 In this case, catalytic [Rh(C 2 H 4 ) 2 Cl] 2 was utilized with ( R )-BINAP as the chiral ligand to provide products 64 from internal alkynes 63 in excellent yields and with high levels of stereocontrol (Scheme 13). Once again, the efficiency and selectivity of the reaction were found to be largely insensitive to both substrate substitution and aryl boronic acid identity.…”
Section: Transition Metal-catalyzed Desymmetrizationsmentioning
confidence: 99%
“…[4g-j, 6] Rhodium-catalyzed 1,4-addition of organoboron reagents to a,b-unsaturated carbonyl compounds offersastraightforward way of constructingC ÀCb onds. [8,9] Various acyclica nd cyclic a,b-unsaturated carbonyl compounds (enones, esters, and amides) have been used for the Rh I -catalyzed 1,4-addition reaction. More recently,t ransition-metal-catalyzed isomerization/ 1,4-addition reactions were developed by Hayashi andc oworkers.…”
mentioning
confidence: 99%
“…Lowering the temperature to room temperature increased the yield to 56 %o wing to the reduced dimerizationo fA L( entry 8). Moreover,e xamining the effect of common solvents in Rh I -catalyzed 1,4-addition reactions (i.e.,T HF,C H 3 CN, toluene,a nd 1,2-dichloroethane (DCE), we found that the yields were not improved (entries [9][10][11][12].V arious kindsofrhodiumcatalysts were also tested {i.e.,[Rh(COD)-OH] 2 ,[ Rh(COE) 2 Cl] 2 (COE = cyclooctene), [Rh(C 2 H 4 ) 2 Cl] 2 ,a nd [Rh(CO) 2 Cl] 2 }, and it was found that [Rh(C 2 H 4 ) 2 Cl] 2 was the best catalyst, ascribed to its easy and irreversiblel igand exchange.…”
mentioning
confidence: 99%